Languages and language use in classical Greek historiography and the Alexander tradition - James, DS (2019)
This thesis examines six ancient historians and one biographer who wrote about Greek contact with the Persian Empire. It explores how these writers explicitly discuss the Greek language in its varying dialects (Chapter One), minor bilingual figures like interpreters and envoys (Chapter Two), and major bilingual individuals who adopted foreign tongues in their own interest (Chapter Three). Previous work in this area has largely been historical in focus, seeking the ‘reality’ behind the text whilst underappreciating any literary aims of the historians. Some scholarship has attempted to move beyond this, at least for certain ancient historians (e.g. Herodotus), but no single study yet exists examining this phenomenon in Greek historiography more broadly, incorporating works at the permeable frontiers of and across the genre to arrive at a more integrated description and analysis. The three thematic chapters are each divided into two sections: one on classical Greek historiography (Herodotus, Thucydides, and Xenophon’s Anabasis); the other on the main surviving historians and biographers of Alexander (Diodorus, Curtius Rufus, Plutarch, Arrian – all from the Roman period). Throughout, I place language in its context by considering it alongside other, cultural, aspects of identity (e.g. nomoi). More generally, I seek to situate details of language and language use in their wider contexts: on a narrative level (why do such details occur where they do?), and on a historical level (how do such details fit into a broader contemporary cultural picture?). Influenced by recent work on ancient identities as well as the ‘literary turn’ in ancient historiographical scholarship – that is, the appreciation that historians were writers crafting their own cultural products, not just chroniclers of events – this thesis employs the insights of narratology and philology to attempt to evaluate the historians’ approaches to language and identity on their own terms and in their own contemporary cultural, political, and literary contexts.